1980
DOI: 10.2135/cropsci1980.0011183x002000020019x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Photosynthesis, Ribulose Bisphosphate Carboxylase, Proteolytic Activity, and Ultrastructure of Soybean Leaves during Senescence1

Abstract: Changes in photosynthesis,rlbulose bisphosphate carboxylase (RuBPCase), and proteolytic activity were followed in the leaves of field-grown soybeans [Giycine max (L.) Merr. cv. Kent] from flowering through senescence. These parameters were followed in relation to changes in leaf resistance, chlorophyll, protein, starch, total N levels, and seed development. In addition, changes in leaf ultrastructure were observed. The initial symptoms of senescence (evident 3 to 4 weeks after flowering) were a decline in phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 0 publications
5
66
1
1
Order By: Relevance
“…Leaf P concentration did not increase until the soil P level exceeded that required for maximum growth. Leaf senescence is often characterized by a large decrease in leaf N during the seed filling period (2,3,7,19,28,29). For all soil P treatments used in this study, there was a large decline in N concentration during the seed filling period (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Leaf P concentration did not increase until the soil P level exceeded that required for maximum growth. Leaf senescence is often characterized by a large decrease in leaf N during the seed filling period (2,3,7,19,28,29). For all soil P treatments used in this study, there was a large decline in N concentration during the seed filling period (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…We observed that net amino acid efflux was generally about 0.250 nmol amino-N.min-'. 10 (15,18,20,28). Thus, our experimental system seems to be physiologically relevant to whole-plant studies.…”
Section: Discussionmentioning
confidence: 97%
“…Naturally occurring leaf senescence is an orderly, and sometimes slow, process. For example, the near complete loss of chlorophyll from senescing soybean leaves, which begins approximately 4 weeks after flowering, is accomplished over a 6 week period (Wittenbach et al, 1980). During soybean leaf senescence, approximately 80% of starch and 90% of soluble protein are lost from the leaves.…”
Section: Senescencementioning
confidence: 99%
“…Numerous biochemical characterizations of increased proteolytic activity during senescence have been presented (Matile and Winkenbach, 1971;Martin and Thimann, 1972;Drivdahl and Thimann, 1977;Wittenbach et al, 1980Wittenbach et al, , 1982Miller and Huffaker, 1982;and reviewed by Feller, 1986), including evidence for activity of both thiol (Miller and Huffaker, 1982;Drivdhal and Thimann, 1977) and serine proteases (Miller and Huffaker, 1982). Further support for an important role for proteases in leaf senescence has come from the identification of senescence-related genes.…”
Section: Senescencementioning
confidence: 99%